Overview of Yellow rice stem borer, Scirpophaga incertulas in Malaysia - Mokhtar, Anis Syahirah; Abdullah, Siti Wan Rasidah (Research Information, 2024)
Rice (Oryza sativa) ranks third among important crops in Malaysia after rubber and oil palm. It is also a staple food consumed around the world. Rice production is mainly limited by pests and diseases particularly rice stem borers where the most common species in Asia are Scirpophaga incertulas (Yellow stem borer), Chilo polychrysus (Black-headed stem borer), Sesamia inferens (Pink stem borer) and Chilo suppressalis (Striped stem borer). The stem borers are major rice pest as they can cause dead heart and white head symptoms leading to heavy yield losses. As of now, practising Integrated Pest Management (IPM) is an effective management strategy of rice stem borer outbreaks and associated crop damage and it is also safe to humans and the environment. This paper is an overview of major rice stem borers in Malaysia, (emphasising S. incertulas) examining their occurrence and distribution, nature of the damage, biology, life cycle and available management strategies.